2001
DOI: 10.1017/s0033291701004068
|View full text |Cite
|
Sign up to set email alerts
|

Different trait markers for schizophrenia and bipolar disorder: a neurocognitive approach

Abstract: Dysfunctions of sensory-perceptual analysis (VBM) and working memory for spatial information distinguished the siblings of schizophrenia patients from the siblings of individuals with bipolar disorder. Verbal recall deficit was present in both groups, suggesting a common impairment of the fronto-hippocampal system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
1
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(133 citation statements)
references
References 35 publications
9
119
1
4
Order By: Relevance
“…Siblings of patients with BD or schizophrenia were impaired relative to controls on the long delay components of a verbal memory test, but performed at control levels on other cognitive domains, including a spatial working memory task. 169 Another group compared working memory and explicit memory of first-degree relatives of patients with BD type I and II and controls unrelated to patients with BD. Although the groups preformed at the same level on a picture learning task, the firstdegree relatives of patients with BD were impaired on the recall and recognition tasks of a verbal learning task in comparison to controls.…”
Section: Cognitive Endophenotypesmentioning
confidence: 99%
“…Siblings of patients with BD or schizophrenia were impaired relative to controls on the long delay components of a verbal memory test, but performed at control levels on other cognitive domains, including a spatial working memory task. 169 Another group compared working memory and explicit memory of first-degree relatives of patients with BD type I and II and controls unrelated to patients with BD. Although the groups preformed at the same level on a picture learning task, the firstdegree relatives of patients with BD were impaired on the recall and recognition tasks of a verbal learning task in comparison to controls.…”
Section: Cognitive Endophenotypesmentioning
confidence: 99%
“…Studies have shown the deficit to be stable over time in people with schizophrenia 3,4 and not an epiphenomenon of antipsychotic medications. [5][6][7] Researchers have also found both remitted schizophrenia patients 7 and healthy first-degree biological relatives of schizophrenia patients [8][9][10][11] to have visual percepts that are unusually vulnerable to a subsequent masking stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent meta-analytic studies concluded that too few studies have compared free recall, cued recall, and recognition for the same test in patients with schizophrenia and their relatives (Whyte et al, 2005;Trandafir et al, 2006) such that no firm conclusions can be drawn for the existence or not of retrieval deficits (Trandafir et al, 2006). Some studies have observed deficits in recognition hits among relatives of schizophrenic patients (Lyons et al, 1995), while others have not (Keri et al, 2001;Sponheim et al, 2004). One study showed that relatives performed worse on cued recall compared with controls (Sponheim et al, 2004).…”
Section: Introductionmentioning
confidence: 99%